2018
DOI: 10.18178/joig.6.1.10-20
|View full text |Cite
|
Sign up to set email alerts
|

Object Recognition in Python and MNIST Dataset Modification and Recognition with Five Machine Learning Classifiers

Abstract: Schools in many parts of the world use robots as social peers in order to interact with children and young students for a rich experience. Such use has shown significant enhancement of children's learning. This project uses the humanoid robot NAO which provides object recognition of colours, shapes, typed words, and handwritten digits and operators. The recognition of typed words provides performance of the corresponding movements in the sign language. Five classifiers including neural networks are used for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…They have used five machine learning algorithms, including neural networks and achieved 87%-98% accuracy on object recognition. 9 A combination of KNN and ANN is used for dragon fruit classification tasks. The study showed that the machine learning method had six times better performance than manual classification.…”
Section: Related Workmentioning
confidence: 99%
“…They have used five machine learning algorithms, including neural networks and achieved 87%-98% accuracy on object recognition. 9 A combination of KNN and ANN is used for dragon fruit classification tasks. The study showed that the machine learning method had six times better performance than manual classification.…”
Section: Related Workmentioning
confidence: 99%
“…In the early stage of video understanding, researchers pay more attention to the features of manual design, which is the basis for encoding the appearance and motion information of video 16 . With the great success of deep neural network in Imagenet 17,18 and object recognition and detection 43,44,45 , many video recognition and classification methods begin to extract features from 2D image convolution network after video frame extraction, and explore the improvement of video classification effect in combination with video optical flow information 20,19,21 . Such methods often process RGB image frames and optical flow image frames respectively, and fuse the features before recognition.…”
Section: Related Workmentioning
confidence: 99%
“…Image processing is a component of the system's lower-level image analysis or computer vision functionality. With the aid of deep learning (DL), fuzzy systems, and improved feature extraction procedures, etc., image processing has made significant advances in recent years [1][2][3][4]. Currently, transformer models are gaining popularity in computer vision tasks.…”
Section: Introductionmentioning
confidence: 99%